Non Malefficence pada Pasien Hipertensi: Analisis Konsep - Kuswati, Ani; Awaludin, Sidik (JURNAL KEPERAWATAN MERSI, 2024)
Background: The principle of nonmaleficence (no harm) means not causing physical and psychological harm/injury to the patient. The principle of nonmaleficence means that health workers in providing health services must always have the intention of helping patients overcome their health problems. Nonmaleficence in hypertensive patients depends on how the nurse or health worker provides assistance or nursing care so as not to cause harm/danger to the patient. Objective: the concept analysis aimed to explore Non-Malefficence pada Pasien Hipertensi. Methods: This concept analysis was carried out with the help of literature about non-maleficence obtained through the Google Scholar and Preplexity databases. The keywords used are "non-maleficence concept" and "hypertension sufferers". The years of publication of books and articles start from 1989 to 2021. Results: An estimated 1.13 billion people worldwide suffer from hypertension, the majority (two-thirds) living in low- and middle-income countries. In 2015, 1 in 4 men and 1 in 5 women suffered from hypertension. Less than 1 in 5 people with hypertension have the problem under control. Conclusion: This concept analysis was carried out using the methods and steps proposed by Walker and Avant. Method of identifying attributes, antecedents and consequences of non-maleficence. This gives rise to the operational definition of mal noneficence, namely a person's moral principles in making decisions to provide treatment/action/therapy with appropriate benefits without causing physical or mental harm, harm or danger.